SISTEM APLIKASI PEMBIAYAAN PINJAMAN DANA TUNAI JAMINAN BPKB SEPEDA MOTOR PADA PT. RADANA FINANCE CABANG BINJAI - Dewi, Sintia; Suriati, Sri; Ambarita, Indah; Lumbanbatu, Katen (STMIK Kaputama, 2017)
PT . Radana Finance Tbk is a company engaged in the field of financial services consumer loans , particularly two-wheel motor vehicles , motorcycles both new and used motorcycles that use guarantees and financing multipurpose reg . PT . Radana Finance Tbk in day - today is inseparable from the process of borrowing the cash . In the data processing still using manual systems . Therefore, the authors take the problem in the field of financing cash loan guarantee BPKB motorcycle In writing the final report , the author makes the design of the new system using VB .NET 2008 and SQL Server 2005 database as well as designing Data Flow Diagrams ( DFD ) , database , data dictionary , context diagrams, tables and Flowmap relations. Applications designed system aims to improve services to the customers of PT. Radana Finance in loan transactions, can process data quickly and accurately. The process of data storage can be better, and can avoid data duplication and facilitate employees in the processing of transaction data.